Estimation and analysis of life annuity premiums with distortion risk measures - Jurado Salazar, Mariana Fernanda (2018)
Although longevity risk has always been tied to life annuities, the continuous improvement of life expectancy and the current low interest and inflation rates, as well as the less favourable equity returns, have unveiled the magnitude of this risk. Hence, life insurers have to rely on management techniques to reduce their exposure to this risk such as natural hedging, reinsurance or derivatives, though they have limitations. As a consequence, the correct pricing of the longevity exposure has become crucial.